2019
DOI: 10.1002/jsfa.9774
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ultrasonic and ball‐milling treatment on cell wall, nutrients, and antioxidant capacity of rose (Rosa rugosa) bee pollen, and identification of bioactive components

Abstract: BACKGROUND: Bee pollen has been regarded as a complete nutritional human dietary supplement but its nutrient absorption and biological effects may be restricted by the complex pollen wall. The aim of this study was to explore the effects of ultrasonic and ball-milling treatment on the release of nutritional components and on in vitro and in vivo antioxidant effects of rose (Rosa rugosa) bee pollen. RESULTS: Bee pollen walls were broken to varying degrees, nutrients were released, and in vitro and in vivo antio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 33 publications
3
27
0
Order By: Relevance
“…However, our study revealed the presence of 3-O-methylkaempferol in rose leaves. Similarly, isorhamnetin and its glucosides were noted in rugosa rose bee pollen [38] and in the leaves, petals, and fruits of other rose species [16,18,39]. However, our report describes the presence of isorhamnetin in R. rugosa leaves.…”
Section: Flavonoid Aglyconessupporting
confidence: 45%
“…However, our study revealed the presence of 3-O-methylkaempferol in rose leaves. Similarly, isorhamnetin and its glucosides were noted in rugosa rose bee pollen [38] and in the leaves, petals, and fruits of other rose species [16,18,39]. However, our report describes the presence of isorhamnetin in R. rugosa leaves.…”
Section: Flavonoid Aglyconessupporting
confidence: 45%
“…Ultrasound-assisted extraction of polyphenols from crude pollen was used by Yang et al [15] and Wu et al [16]. Yang et al [15] used ultrasonic and ball-milling treatment to improve the extraction of bioactive compounds from rose bee pollen, while Wu et al [16] used ultrasonic and high shear technique for improving the extraction of amino acids, fatty acids, protein, crude fat, reducing sugar, β-carotene, calcium, iron, zinc and selenium, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The ORAC analysis indicated that compounds 1 – 4 are major contributors to the high antioxidant capacity of strawberry pollen. Similarly, the presence of compounds 1 (or 2 ), 4 , 5 and N′ , N″ , N″′ ‐tri‐caffeoylspermidine and the high antioxidant activities including ORAC were reported in rose bee pollen extracts 52 …”
Section: Discussionmentioning
confidence: 79%